2011
DOI: 10.1103/physrevb.84.144506
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic magnetic order of the Eu sublattice in single crystals of EuFe2xCoxAs

Abstract: Here, we present a combination of magnetization and magnetic torque experiments to investigate the magnetic orders in undoped EuFe2As2 and Co doped EuFe1.8Co0.2As2 single crystals. Although at low temperatures typical results for an antiferromagnetic (AFM) state in EuFe2As2 were found, our data strongly indicate the occurrence of a canted antiferromagnetic (C-AFM) order of the Eu 2+ moments between 17 K and 19 K, observed even in the lowest studied magnetic fields. However, unlike in the parent compound, no lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 45 publications
6
39
0
Order By: Relevance
“…41,42 On the other hand, the magnetic ground state of the Eu 2+ spins shows a systematic evolution with Co doping. Consistent with previous studies on Eu(Fe 1−x Co x ) 2 As 2 using Mössbauer spectroscopy and magnetic torque, 19,43 the magnetic ground state of the Eu 2+ moments is found to depend strongly on the Co doping level. For relatively low Co doping levels (the area in red), the ground-state magnetic structure of Eu is the Atype AFM structure (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…41,42 On the other hand, the magnetic ground state of the Eu 2+ spins shows a systematic evolution with Co doping. Consistent with previous studies on Eu(Fe 1−x Co x ) 2 As 2 using Mössbauer spectroscopy and magnetic torque, 19,43 the magnetic ground state of the Eu 2+ moments is found to depend strongly on the Co doping level. For relatively low Co doping levels (the area in red), the ground-state magnetic structure of Eu is the Atype AFM structure (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3 et al [2] or a canting of the Eu 2+ moments from the c-axis was suggested by Guguchia et al [6] and Błachowski et al [7]. It is worth mentioning that Jiang et al [2], Niclas et al [4] and Guguchia et al [6] found a spin reorientation from an AF to a ferromagnetic (F) arrangement upon application of external magnetic fields or hydrostatic pressure.…”
mentioning
confidence: 89%
“…3 et al [2] or a canting of the Eu 2+ moments from the c-axis was suggested by Guguchia et al [6] and Błachowski et al [7]. It is worth mentioning that Jiang et al [2], Niclas et al [4] and Guguchia et al [6] found a spin reorientation from an AF to a ferromagnetic (F) arrangement upon application of external magnetic fields or hydrostatic pressure. The only two reports of field-temperature H-T magnetic phase diagrams that we are aware of are those obtained for superconducting Eu(Fe 0.89 Co 0.11 ) 2 As 2 [2] and nonsuperconducting Eu(Fe 0.9 Co 0.1 ) 2 As 2 [6] crystals.…”
mentioning
confidence: 89%
“…In comparison, an antiferromagnet can be easily tuned into a ferromagnet by application of a high magnetic field [26,27]. However, in this case not an itinerant antiferromagnetic spin density wave, but localized moments order ferromagnetically in these compounds.…”
mentioning
confidence: 99%